2022
DOI: 10.1002/ccr3.6402
|View full text |Cite
|
Sign up to set email alerts
|

A challenging case of rheumatoid arthritis‐associated aortitis presenting with erythema nodosum after ST‐segment elevation myocardial infarction: A case report

Abstract: Rheumatoid arthritis is a systemic inflammatory disease that has many extraarticular manifestations. Cardiovascular involvement, including coronary vasculitis and aortitis and skin lesion of erythema nodosum are uncommon findings of patients with rheumatoid arthritis, and thus, it is challenging for diagnosis of this case from those unusual extra-articular presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Rheumatoid arthritis can have numerous extra-articular manifestations, such as erythema nodosum, aortitis, myocarditis, pericardial effusion, stroke, arrhythmias, and congestive cardiac failure. The absence of these features and a negative rheumatoid factor and anti-CCP report helped us rule out the diagnosis of rheumatoid arthritis [ 7 , 8 ]. Furthermore, the SSS and biopsy reports, along with the drastic symptomatic improvement in arthralgia seen immediately after the first dose of corticosteroids, aided us in substantiating the diagnosis of BL Hansen's disease in type 2 reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis can have numerous extra-articular manifestations, such as erythema nodosum, aortitis, myocarditis, pericardial effusion, stroke, arrhythmias, and congestive cardiac failure. The absence of these features and a negative rheumatoid factor and anti-CCP report helped us rule out the diagnosis of rheumatoid arthritis [ 7 , 8 ]. Furthermore, the SSS and biopsy reports, along with the drastic symptomatic improvement in arthralgia seen immediately after the first dose of corticosteroids, aided us in substantiating the diagnosis of BL Hansen's disease in type 2 reactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, RA can rarely manifest with erythema nodosum. There have been only a few reported cases of EN in patients with rheumatoid arthritis [30,31]. A study of 130 patients by Karpova et al who were referred with a diagnosis of erythema nodosum showed that 35% were secondary to infectious causes and the other 35% due to Löfgren syndrome.…”
Section: Discussionmentioning
confidence: 99%